Сlostridium difficile Infection in a COVID-19 Patient - A. A. Timofeeva; Yu. O. Shulpekova; V. M. Nechaev; M. R. Skhirtladze (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The clinical observation highlights plausible compound origins of diarrhoea, fever and neutrophilic leucocytosis in COVID-19 and the rationale to exclude Clostridium difficile infection in such patients.Key points. A 57-yo female patient was admitted in May 2020 with the complaints of 39 °C fever, general weakness, polymyalgia, diarrhoea to 3–4 times a day (mushy stool, no morbid inclusions). Initial diarrhoea was non-severe and likely triggered by the coronavirus infection. A background antibiotic and putative-immunosuppressive therapy proceeded with watery diarrhoea to 7–8 times a day and C. difficile toxins A and B detected in stool. The C. difficile infection relapsed on day 10 of vancomycin withdrawal and associated with elevated body temperature, diarrhoea and neutrophil leucocytosis; signs of colitis determined in ultrasound and CT. Exacerbation was successfully treated in a repeated metronidazole-combined vancomycin course.Conclusion. Patients with COVID-19 are at risk of clostridial colitis due to massive antibiotic, systemic glucocorticoid and biologics-based therapy they receive. The opportunistic bacterial infection of C. difficile often proceeds undetected due to its potential mirroring of COVID-19 presentation. A screening algorithm in COVID-19 patients with diarrhoea should imply steps for C. difficile detection.